Make or Buy? Approaches to Financial Market Integration - Michael Gavin; Ricardo Hausmann (Inter-American Development Bank, Office of the Chief Economist, 1997)
The sharp differences between financial markets as they exist in Latin America and how we might expect them to look under full integration suggest that the financial constraints on Latin American economic development have much to do with the region`s financial markets` incomplete integration in the world financial system. This paper suggests that the underlying cause of Latin America`s limited integration with world financial markets is not explicit barriers to international financial transactions. Rather, weaknesses in the domestic financial markets that would be called upon to intermediate international capital flows impedes integration. An appropriate financial integration approach can strengthen and deepen the domestic financial system by permitting indirect imports of the requisite public goods (provided by the banks` home countries) and by allowing a greater diversification of national risks.
Keywords: 330